Daur Khaţ an-Naskh fī Tanmiah Maharah al-Kitābah bi al-Lughah al-ʽArabiyah: Murājaʽah Manhajiyah li al-Adabiyat - Nurazizah Bancin; Anwar Sidik; Fitri Mawaddah Bako (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
مستخلص البحث: الخط النسخي يُعد من أسهل أنواع الخطوط العربية تعلُّمًا وأكثرها استخدامًا في المجال التعليمي، مما يجعله موضوعًا مناسبًا للدراسة من حيث أثره في تنمية مهارة الكتابة لدى الطلاب. يهدف هذا البحث إلى تحليل دور تعليم الخط النسخ في تطوير مهارات الكتابة باللغة العربية، من خلال مراجعة منهجية للأدبيات. يعتمد البحث على منهج المراجعة المنهجية للأدبيات (Systematic Literature Review - SLR) بتحليل الدراسات السابقة ذات الصلة. تم جمع البيانات من مقالات علمية ومجلات أكاديمية وتقارير بحثية ركزت على تعليم الخط النسخ ومهارة الكتابة. أظهرت النتائج أن تعليم الخط النسخ لا يُحسن فقط من جودة الكتابة، بل يعزز الجوانب الجمالية والثقافية لدى الطلاب. كما ظهرت عوامل مساعدة مثل وجود المعلمين المؤهلين والوسائل المناسبة، وأخرى معوقة مثل قلة الوقت في المناهج الدراسية. توصي الدراسة بدمج الخط النسخ بشكل أوسع ضمن مناهج تعليم اللغة العربية. الكلمات المفتاحية: مراجعة منهجية (SLR) ، خط النسخ، مهارة الكتابة Abstract: Naskh script is one of the easiest types of Arabic scripts to learn and the most widely used in the educational field, making it a suitable topic for study in terms of its impact on the development of students' writing skills. This research aims to analyze the role of teaching Naskh calligraphy in developing Arabic writing skills through a systematic literature review. The research adopts the Systematic Literature Review (SLR) approach by analyzing previous relevant studies. Data were collected from scientific articles, academic journals, and research reports that focused on teaching calligraphy and writing skills. The results showed that teaching calligraphy not only improves the quality of writing, but also enhances students' aesthetic and cultural aspects. Helping factors such as the presence of qualified teachers and appropriate tools, and hindering factors such as lack of time in the curriculum were also found. The study recommends integrating calligraphy more widely into the Arabic language curriculum. Keywords: Systematic Literature Review, Naskh Script, Writing Skills